2012
DOI: 10.1111/j.1740-8709.2011.00396.x
|View full text |Cite
|
Sign up to set email alerts
|

Provision of weight management advice for obese women during pregnancy: a survey of current practice and midwives' views on future approaches

Abstract: A semi-structured, web-based questionnaire was developed to survey midwives (n = 241) employed by NHS Tayside, UK, to identify current practice and views on weight management of obese women during pregnancy and the puerperium. A total of 78 (32%) midwives submitted responses following email invitation. Most respondents (79%) reported always calculating women's body mass index (BMI) at booking, with 73% routinely explaining the BMI category. In terms of future practice for obese women, although few respondents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
42
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 4 publications
(6 reference statements)
2
42
0
Order By: Relevance
“…This may be achieved through the development of a relationship-centred approach to pregnancy care, by focussing on individual needs and concerns (Scottish Government, 2010a). In addition, as midwives and other health professionals feel illequipped to communicate with and care for women effectively (Olander et al, 2011;Oteng-Ntim et al, 2010;Davis et al, 2012;Heslehurst et al, 2013b;Macleod et al, 2013), a framework that considers the needs of all individuals within a relationship may be considered.…”
Section: Discussionmentioning
confidence: 99%
“…This may be achieved through the development of a relationship-centred approach to pregnancy care, by focussing on individual needs and concerns (Scottish Government, 2010a). In addition, as midwives and other health professionals feel illequipped to communicate with and care for women effectively (Olander et al, 2011;Oteng-Ntim et al, 2010;Davis et al, 2012;Heslehurst et al, 2013b;Macleod et al, 2013), a framework that considers the needs of all individuals within a relationship may be considered.…”
Section: Discussionmentioning
confidence: 99%
“…However, consistent with previous research, it appears that this may not be the case. 29,30,31 A number of surveys have identified that fewer than half of the healthcare providers frequently discuss risks associated with women about being above a healthy weight in pregnancy. 29,30,31 These results support previous studies suggesting that health professionals should highlight the increased risk associated with being overweight before pregnancy and gaining excess weight.…”
Section: Discussionmentioning
confidence: 99%
“…29,30,31 A number of surveys have identified that fewer than half of the healthcare providers frequently discuss risks associated with women about being above a healthy weight in pregnancy. 29,30,31 These results support previous studies suggesting that health professionals should highlight the increased risk associated with being overweight before pregnancy and gaining excess weight. 15,16,29,32 Although this is an important step, explicitly linking behavior and susceptibility to these risk is required to ensure that women recognize their personal vulnerability to these risks.…”
Section: Discussionmentioning
confidence: 99%
“…Women want weight-related information (Olander et al, 2011) including information on weight management services from their midwife (Patel et al, 2013). However, midwives report lacking confidence to raise the issue of weight management with women (Macleod et al, 2013). Midwives may also perceive management of gestational weight gain as low priority and have concerns about the psychological impact of focusing on weight gain during pregnancy (Willcox et al, 2012).…”
Section: Introductionmentioning
confidence: 99%